STRUKTUR KOMUNITAS GASTRPODA DI SUNGAI SANGKIR ANAK SUNGAI ROKAN KIRI KABUPATEN ROKAN HULU - Purwanti, Tika; Yolanda, Rofiza; Purnama, Arief Anthonius (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study of the community and structure of gastropods in river tributaries Sangkir Rokan Left has been conducted from December to January 2015 with survey method meanwhile sampling technique with purposive random sampling in three sites, upstream, midstream and downstream. Samples were collected with eckman grab from 3 site with 5 repetitions. Result showed, 4 families with 6 species were found, meanwhile abundance 151,1 to 853,2individuals/ m2, diversity index 0.68 to 1.31, Similarity 0.7 to 0.98 and dominance 0.29 to 0.52. Physical and chemical parameters that influence is the temperature of 280C, pH 6, dissolved oxygen 5.25 to 5.55 mg/l and organic substrate concentration 0.22% - 2.43%.